Alcohol outlet density and alcohol related hospital admissions in England: a national small‐area level ecological study. (19th August 2018) - Maheswaran, Ravi; Green, Mark A.; Strong, Mark; Brindley, Paul; Angus, Colin; Holmes, John
Abstract: Background and aims: Excessive alcohol consumption has a substantial impact on public health services. A key element determining alcohol availability is alcohol outlet density. This study investigated the relationship between on‐trade and off‐trade outlets and hospital admission rates in local neighbourhoods. Design: National small‐area level ecological study. Setting and participants: All 32 482 lower layer super output census areas (LSOAs) in England (42 227 108 million people aged 15+ years). Densities for six outlet categories (outlets within a 1‐km radius of residential postcode centroids, averaged for all postcodes within each LSOA) were calculated. Measurements: Main outcome measures were admissions due to acute or chronic conditions wholly or partially attributable to alcohol consumption from 2002/03 to 2013/14. Findings: There were 1 007 137 admissions wholly, and 2 153 874 admissions partially, attributable to alcohol over 12 years. After adjustment for confounding, higher densities of on‐trade outlets (pubs, bars and nightclubs; restaurants licensed to sell alcohol; other on‐trade outlets) and convenience stores were associated with higher admission rate ratios for acute and chronic wholly attributable conditions. For acute wholly attributable conditions, admission rate ratios were 13% (95% confidence interval = 11–15%), 9% (7–10%), 12% (10–14%) and 10% (9–12%) higher, respectively, in the highest relative to the lowest density categories by quartile. For chronic wholly attributable conditions, rate ratios were 22% (21–24%), 9% (7–11%), 19% (17–21%) and 7% (6–9%) higher, respectively. Supermarket density was associated with modestly higher acute and chronic admissions but other off‐trade outlet density was associated only with higher admissions for chronic wholly attributable conditions. For partially attributable conditions, there were no strong patterns of association with outlet densities. Conclusions: In England, higher densities of several categories of alcohol outlets appear to be associated with higher hospital admission rates for conditions wholly attributable to alcohol consumption.